Generation of monoclonal antibody against protein phosphatase 5 - Malanchuk, O.M.; Ovcharenko, G.V.; Tykhonkova, I.O.; Khoma, O.S.; Chorna, U.V.; Rybak, M.Yu.; Palchevskyy, S.S. (Вiopolymers and Cell, 2013)
Aim. Serine/threonine protein phosphatase 5 (PP5) is a unique member of serine/threonine phosphatase family, comprises a regulatory tetratricopeptide repeat (TPR) domain and regulates many cell signaling pathways. Here, we describe the development of a PP5 specific monoclonal antibody (mAb) and characterize its suitability for Western blotting and immunoprecipitation. Methods. Hybridoma technology has been used for monoclonal antibody generation. Immunization was carried out with recombinant mouse PP5 expressed in Escherichia coli as a GST-tagged fusion protein. Results. mAb against PP5 has been generated. Conclusions. Generated mAb specifically recognizes recombinant and endogenous mouse and rat PP5 and is suitable for Western blotting and immunoprecipitation. This mAb will be useful tool for investigations of PP5 physiological role.